In vitro anticancer activity of microbial isolates from diverse habitats - Angel Treasa Thomas; Josyula Venkata Rao; Volety Mallikarjuna Subrahmanyam; Hariharapura Raghu Chandrashekhar; Naseer Maliyakkal; Tukaram Kedar Kisan; Alex Joseph; Nayanabhirama Udupa (Universidade de São Paulo, 2011)
Extracts from natural products, especially microorganisms, have served as a valuable source of diverse molecules in many drug discovery efforts and led to the discovery of several important drugs. Identification of microbial strains having promising biological activities and purifying the bio-molecules responsible for the activities, have led to the discovery of many bioactive molecules. Extracellular, as well as intracellular, extracts of the metabolites of thirty-six bacterial and twenty-four fungal isolates, grown under unusual conditions such as high temperature, high salt and low sugar concentrations, were in vitro tested for their cytotoxic potential on various cancer cell lines. The extracts were screened on HeLa and MCF-7 cell lines to study the cytotoxic potential. Nuclear staining and flow cytometric studies were carried out to assess the potential of the extracts in arresting the cell cycle. The crude ethylacetate extract of isolate F-21 showed promising results by MTT assay with IC50 as low as 20.37±0.36 µg/mL on HeLa, and 44.75±0.81 µg/mL on MCF-7 cells, comparable with Cisplatin. The isolate F-21 was identified as Aspergillus sp. Promising results were also obtained with B-2C and B-4E strains. Morphological studies, biochemical tests and preliminary chemical investigation of the extracts were also carried out. Extratos de produtos naturais, especialmente de microrganismos, constituíram-se em fonte valiosa de diversas moléculas em muitas descobertas de fármacos e levaram à descoberta de fármacos importantes. A identificação de espécies microbianas que apresentam atividade biológica e a purificação de biomoléculas responsáveis pelas atividades levou à descoberta de muitas moléculas bioativas. Extratos extracelulares tanto quanto intracelulares de metabólitos de 36 isolados de bactérias e 24 isolados de fungos, que cresceram sob condições não usuais, como alta temperatura, alta concentração de sal e baixa concentração de açúcar, foram testados in vitro quanto ao seu potencial citotóxico em várias linhagens de câncer. Os extratos foram ensaiados em células HeLa e MCF-7 para o estudo do potencial citotóxico. A coloração nuclear e os estudos de citometria de fluxo foram realizados para avaliar o potencial dos extratos em bloquear o ciclo celular. O extrato bruto em acetato de etila do isolado F-21 mostrou resultados promissores no ensaio de MTT, com IC50 de 20,37±0,36 µg/mL em células HeLa e 44,.75±0,81 µg/mL em células MCF-7, comparativamente à cisplatina. O isolado F-21 foi identificado como Aspergillus sp. Resultados promissores foram obtidos com cepas B-2C e B-4E. Realizaram-se, também, estudos morfológicos, testes bioquímicos e investigação química preliminar dos extratos.